Ta’allum al-Lughah al-Àrabiyyah fi Dhau’ al-Biah li Tahfiz at-Thullab a’la al-Tahaddus biha fi al-Maáhid al-Islamiyyah Sumatra al-Gharbiyyah - Suharmon, Suharmon; Salam, Muhammad Yusuf; Hasaniyah, Nur (Institut Agama Islam Negeri Curup, 2022)
This study aims to describe the environment-based studentsâ€™ motivation to learn Arabic in Islamic Boarding schools in West Sumatra. Motivation is seen from its intrinsic and extrinsic aspects. This research employed qualitative approach with data collection techniques carried out by observation, interviews, documentation, and questionnaires. Data analysis techniques were carried out by triangulation of observational data, document analysis, documentation, and descriptive statistic. The findings indicate that Islamic boarding schools in West Sumatra were employing environment-based Arabic learning and it was evident that the approach improves studentsâ€™ speaking skills and generates motivation to them. Intrinsic motivation encourages student to speak arabic, which is indicated by theÂ desire to discuss arabic languange materials and is categorized as â€œ very well â€.â€œ student learning desireâ€was also raised on the aspek â€œseriousness of doing learning tasksâ€ which is showing at the â€œvery wellâ€category, and on the aspect of â€œstudentsâ€™ desire to progressâ€ showed the â€œgoodâ€ category.Â In short, the environmental approach sheds light on learning Arabic as it improves studentsâ€™ engagement in speaking Arabic.